Efficacy and safety of anlotinib plus penpulimab as second-line treatment for small cell lung cancer: A multicenter, open-label, single-arm phase II trial - Zhang, Changgong; Chen, Jianhua; Wu, Huijuan; Wang, Jun; Gao, Liying; Zhao, Jun; Sun, Yan; Jia, Zhongyao; Mu, Xinlin; Bai, Chunmei; Wang, Rui; Wu, Kailiang; et al. (Cancer pathogenesis and therapy, 2024)
Currently, the need for new therapeutic strategies involving programmed cell death protein-1 (PD-1) monoclonal antibodies in the second-line setting of small cell lung cancer (SCLC) is urgent. This study aimed to evaluate the efficacy and safety of anlotinib plus penpulimab as a second-line treatment for patients with SCLC who progressed after first-line platinum-based chemotherapy. This study included the patients from Cohort 4 of a single-arm, open-label, multicenter, phase II clinical trial. A safety run-in phase was performed under anlotinib (10/12 mg quaque die [QD], days 1–14) plus penpulimab (200 mg intravenously [IV], day 1) in a 21-day cycle, followed by the formal trial in which the patients received anlotinib (12 mg QD, days 1–14) plus penpulimab (200 mg IV, day 1) in a 21-day cycle. The primary endpoint of the safety run-in phase was safety. The primary endpoint of the formal trial phase was the objective response rate (ORR). From April 28, 2020, to November 24, 2020, 21 patients were enrolled from 11 hospitals, including 2 in the safety run-in phase and 19 in the formal trial phase. In the formal trial phase, the ORR was 42.1% (8/19; 95% confidence interval [CI]: 17.7–66.6%). The median progression-free survival was 4.8 months (95% CI: 2.9–11.3 months), and the median overall survival was 13.0 months (95% CI: 4.6–not applicable [NA] months). The incidence of ≥grade 3 treatment-related adverse events (TRAEs) was 52.4% (11/21), and the incidence of treatment-related serious adverse events (AEs) was 28.6% (6/21). Two AE-related deaths occurred. The most common AEs were hypertension (57.1%, 12/21), hypothyroidism (42.9%, 9/21), and hypertriglyceridemia (38.1%, 8/21). In patients with SCLC who progressed after first-line platinum-based chemotherapy, the second-line anlotinib plus penpulimab treatment demonstrates promising anti-cancer activity and a manageable safety profile, which warrants further investigation. No. NCT04203719, https://clinicaltrials.gov/. [Display omitted] •Anlotinib plus penpulimab shows promising anti-cancer activity and acceptable safety profile in the 2nd-line treatment of small cell lung cancer (SCLC).•Patients who underwent the anlotinib plus penpulimab regimen had an objective response rate (ORR) of up to 42.1% (95% confidence interval [CI]: 17.7–66.6%), a median progression-free survival (PFS) of 4.8 months (95% CI: 2.9–11.3 months), and a median overall survival (OS) of 13.0 months (95% CI: 4.6–not applicable [NA] months).•The anlotinib plus penpulimab regimen warrants further investigation for the treatment of patients with stage SCLC who progressed after first-line platinum-based chemotherapy.